Nilai Estetika dan Cita Rasa Makanan dalam Penyajian Makizuki Musim Gugur pada TV Champion Jepang - Theng Anita Christianawati (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2018)
This research discusses the aesthetic value and taste of the food served in autumn makizushi as shown in TV Champion Japan. It aims to find out the aesthetic value and taste of autumn makizushi, because there are several types of sushi based on the season they are served. The video data were taken from the first episode of Sushi King series of TV Champion, produced by TV Tokyo Japan. The type of this study is descriptive qualitative. The result of the study show that there are severalÂ characteristics of aesthetically served makizushi, i.e.; unity, symmetry, harmony, balance and contrast. In addition, there are three characteristics which define the aestheticÂ value of makizushi taste; unity, harmony and contrast.Keywords : Aesthetic value, Food Aesthetic, Sushi, maki-zushi, Tv Champion Japan